Permanent Peace Amid The Warlike World - Babasyan, Tigran (European Scientific Journal, ESJ, 2017)
Until now the dichotomy of war and peace has tracked two paths: one in tune with the Roman maxim Â«In peace prepare for warÂ» and the other begotten by the ongoing apocalyptic craze for the end of the world and could be tentatively worded like this: â€œWage wars to get peace.â€ Meanwhile there is a flexible and fairly feasible construct to operate in order to reach the balance in war- and -peace things. It is the cause-and- effect relation where war always stands for the effect that, weirdly enough, stems from peace. Does it mean that the real cause of war is engendered in peace? It usually is that way if the peace is established on a loose soil: but when built on the solid ground it devours all those who are in the way of peace. We mean the river of eternal life flowing between the two dichotomic banks: â€œI will send peace flowing over her (Jerusalem) like a river, and the wealth of nations like a stream in flood.â€ (Isaiah 66:12) (The New English Bible,1970). How to reach the banks of this river of disambiguation will be the thrust of our deliberations below.